The green seaweed Ulva: tomorrow’s “wheat of the sea” in foods, feeds, nutrition, and biomaterials - 1. Laurie C. Hofmann, Sylvia Strauss, Muki Shpigel, Lior Guttman, Dagmar B. Stengel, Céline Rebours, Natasha Gjorgovska, Gamze Turan, Karina Balina, Gabrielle Zammit, Jessica M. M. Adams, Umair Ahsan, Angela G. Bartolo, John J. Bolton, Rosário Domingues, Ömerhan Dürrani, Orhan Tufan Eroldogan, Andreia Freitas, Alexander Golberg, Kira I. Kremer, Francisca Marques, Massimo Milia, Sophie Steinhagen, Ekin Sucu, Liliana Vargas-Murga, Shiri Zemah-Shamir, Ziv Zemah-Shamir and Antonio J. Meléndez-Martínez (Taylor & Fransis, 2024)
Ulva, a genus of green macroalgae commonly known as sea lettuce, has long been recognized for its nutritional benefits for food and feed. As the demand for sustainable food and feed sources continues to grow, so does the interest in alternative, plant-based protein sources. With its abundance along coastal waters and high protein content, Ulva spp. have emerged as promising candidates. While the use of Ulva in food and feed has its challenges, the utilization of Ulva in other industries, including in biomaterials, biostimulants, and biorefineries, has been growing. This review aims to provide a comprehensive overview of the current status, challenges and opportunities associated with using Ulva in food, feed, and beyond. Drawing on the expertise of leading researchers and industry professionals, it explores the latest knowledge on Ulva’s nutritional value, processing methods, and potential benefits for human nutrition, aquaculture feeds, terrestrial feeds, biomaterials, biostimulants and biorefineries. In addition, it examines the economic feasibility of incorporating Ulva into aquafeed. Through its comprehensive and insightful analysis, including a critical review of the challenges and future research needs, this review will be a valuable resource for anyone interested in sustainable aquaculture and Ulva’s role in food, feed, biomaterials, biostimulants and beyond.
Keywords: ulva, food; feed; aquafeed; nutrition; biomaterials; biorefinery; seaweed